ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI KARET DI DESA AIR UPAS KECAMATAN AIR UPAS KABUPATEN KETAPANG - Munte, Robin Junaif; Aritonang, Marisi; Oktoriana, Shenny (Fakultas Pertanian Universitas Tanjungpura, 2020)
ABSTRACTThis research was conducted with the aim to find out what factors influence the income of rubber farms in Air Upas Village, Air Upas District, Ketapang Regency. This research was conducted on 85 rubber farmers which were determined by the Accidental Sampling method. In this study two types of variables are used, namely the dependent variable and the independent variable. The dependent variable is the income of farmers while the independent variable is the area of land, the amount of labor, the age of rubber plants, the age of rubber farmers, the cost of farming and the selling price. Data analysis in this study was carried out using multiple linear regression analysis and statistical t test with associative descriptive methods. The results of this study indicate that the area of land, age of rubber farmers, and selling price significantly influence the income of rubber farmers, while the variable number of workers, age of rubber plants,and farming costs does not significantly influence the income of rubber farmers in Air Upas Village, Air Upas District Ketapang Regency.